Nintedanib regulates miR-23b-3p/TGFBR2 axis and competitively binds to TGFBR2 protein, inhibiting EMT process in human pterygium cells - Ke-Ke Zhang; Meng Li; Yan-Hong Liao; Xiao-Tian Liu; Yong-Bo Bao; Yan Gong (International Journal of Ophthalmology)
AIM: To investigate the effects of nintedanib on epithelial-mesenchymal transition (EMT) in cells derived from pterygium, aiming to explore its potential as a pharmacological intervention for pterygium treatment. METHODS: Primary human pterygium epithelial cells (hPEC) and human conjunctival epithelial (hCJE) cells were isolated from patients, cultured, and characterized. The impact of nintedanib on transforming growth factor beta (TGF-β)-induced EMT was assessed by examining the expression of EMT markers such as vimentin and E-cadherin. Additionally, the modulation of the miR-23b-3p/transforming growth factor beta receptor 2 (TGFBR2)/Smad2 pathway by nintedanib was investigated to elucidate its potential antifibrotic mechanism. RESULTS: The expression of miR-23b-3p gene in hCJE cells was significantly higher than that in hPEC cells. Nintedanib effectively mitigated TGF-β-induced EMT in cells derived from pterygium, as evidenced by the downregulation of vimentin and upregulation of E-cadherin. When the nintedanib concentration exceeded 1 μmol/L, it significantly suppressed the proliferation of hPEC cells and significantly inhibited the migration distance of hPEC cells within 48h (P<0.01). The immunoprecipitation experiment showed that nintedanib modulated the TGFBR2 protein's response to TGF-β independently of miR-23b-3p. Both nintedanib and transfection with miR-23b-3p mimic significantly inhibited the expression levels of phosphorylated Smad2, snail homolog 1 (Drosophila, SNAIL), and SNAI2 (also known as SLUG, snail family transcriptional repressor 2) proteins. CONCLUSION: Nintedanib is found to modulate the miR-23b-3p/TGFBR2/Smad2 pathway, suggesting a novel antifibrotic mechanism. These findings collectively highlight nintedanib's therapeutic potential in managing pterygium, marking a significant step toward non-surgical treatment options. Nintedanib may offer a targeted pharmacological treatment that could complement or reduce the need for surgical interventions.